Nafamostat has anti-asthmatic effects associated with suppressed pro-inflammatory gene expression, eosinophil infiltration and airway hyperreactivity - Allam, Venkata Sita Rama Raju; Waern, Ida; Taha, Sowsan; Akula, Srinivas; Wernersson, Sara; Pejler, Gunnar (Frontiers in Immunology, 2023)
Asthma is characterized by an imbalance between proteases and their inhibitors. Hence, an attractive therapeutic option could be to interfere with asthma-associated proteases. Here we exploited this option by assessing the impact of nafamostat, a serine protease known to neutralize mast cell tryptase. Nafamostat was administered in a mouse model for asthma based on sensitization by house dust mite (HDM) extract, followed by the assessment of effects on airway hyperreactivity, inflammatory parameters and gene expression. We show that nafamostat efficiently suppressed the airway hyperreactivity in HDM-sensitized mice. This was accompanied by reduced infiltration of eosinophils and lymphocytes to the airways, and by lower levels of pro-inflammatory compounds within the airway lumen. Further, nafamostat had a dampening impact on goblet cell hyperplasia and smooth muscle layer thickening in the lungs of HDM-sensitized animals. To obtain deeper insight into the underlying mechanisms, a transcriptomic analysis was conducted. This revealed, as expected, that the HDM sensitization caused an upregulated expression of numerous pro-inflammatory genes. Further, the transcriptomic analysis showed that nafamostat suppressed the levels of multiple pro-inflammatory genes, with a particular impact on genes related to asthma. Taken together, this study provides extensive insight into the ameliorating effect of nafamostat on experimental asthma, and our findings can thereby provide a basis for the further evaluation of nafamostat as a potential therapeutic agent in human asthma.